Contemporary discourse on gender equality in Indonesia: an analysis of the views of Siti Musdah Mulia - ., Tias Nurul Fauziah; Ali, Muhammad Mumtaz (IIUM Press, International Islamic University Malaysia, 2017)
This study is an attempt to study and analyze the contemporary discourse on gender equality in Indonesia developed by Indonesian Muslim intellectual, Siti Musdah Mulia. To achieve this, it explores and examines the views of Siti Musdah Mulia on gender equality. Musdah is one of the leading Muslim feminists in Indonesia but her thought on feminism and gender equality are considered most controversial. They are propagated among her students at IAIN and also in the organizations that she is a member of such as Fatayat NU, LKAJ (Institute for Study of Religion and Gender), IRCP (Indonesian Conference on Religion and Peace), Megawati Institute even to the levels of government, namely the Ministry of Religion, in which she is the coordinator to the team drafting the CLD (Counter Legal Draft) for KHI (Compilation of Islamic Legal Laws). In this research, the method that has been adopted is textual analysis, using descriptive and analytical methods by referring to numerous works on the subject. It is contended that her thoughts on feminism and gender equality are not independent but influenced by liberal movement and presented as Islamic thought. Hence, this study analyses and criticizes her views from an Islamic perspective. This study reveals that Musdah’s stand of gender equality is based on humanism i.e. human rights and equality in quantity. This basis is used by her to read the principle of Tawḥīd, the Qur’an and Islamic jurisprudence in order to produce a new interpretation of Islamic teachings to support gender equality as understood by gender feminism. It is concluded that Musdah’s views have considerably deviated from Islamic teachings and are destructive towards the Muslim family institution.